2016
DOI: 10.1109/taslp.2016.2521486
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Channel Non-Intrusive C50 Estimator Correlated With Speech Recognition Performance

Abstract: Abstract-Several intrusive measures of reverberation can be computed from measured and simulated room impulse responses, over the full frequency band or for each individual mel-frequency subband. It is initially shown that full-band clarity index C50 is the most correlated measure on average with reverberant speech recognition performance. This corroborates previous findings but now for the dataset to be used in this study. We extend the previous findings to show that C50 also exhibits the highest mutual infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In this paper we limit our discussion to the case of additive noise and the effects of speech codecs. Other degradations such as reverberation and effects of noise suppression are not considered here but the reader is referred to the appropriate literature elsewhere on nonintrusive reverberation estimation such as [43]. The remainder of this paper is organized as follows, in Section II we review the non-intrusive LCQA method [22] and describe LCIA, a development of LCQA for non-intrusive speech intelligiblity assessment.…”
Section: A Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we limit our discussion to the case of additive noise and the effects of speech codecs. Other degradations such as reverberation and effects of noise suppression are not considered here but the reader is referred to the appropriate literature elsewhere on nonintrusive reverberation estimation such as [43]. The remainder of this paper is organized as follows, in Section II we review the non-intrusive LCQA method [22] and describe LCIA, a development of LCQA for non-intrusive speech intelligiblity assessment.…”
Section: A Overviewmentioning
confidence: 99%
“…A non-intrusive method for speech quality and intelligibility estimation of reverberant and de-reverberated speech was presented in [41] and a method for predicting the intelligibility of reverberant speech for cochlear implant listeners was presented in [42]. A recent method for non-intrusive estimation of the C50 room acoustic parameter was presented in [43] and shown to correlate with speech quality and speech recognition performance. The low complexity speech intelligibility algorithm (LCIA) is a datadriven non-intrusive measure that has been shown to have a high per-condition correlation with subjective intelligibility scores of noisy and noise suppressed speech [44].…”
Section: Introductionmentioning
confidence: 99%
“…Tsilfidis et al showed that C50 and D50 can be used to predict phoneme recognition rate [15]. Parada et al proposed a blind C50 estimator that is correlated with phoneme recognition [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, in many cases, the clean signal is not available (e.g., audio record or voice received in telephony), so that non-intrusive (or reference-free) measures are required. Most of them, like NIRA [6] or NISI [7], are based on machinelearning techniques and derive indicators from a large set of signal parameters by maximizing the correlation with reference indicators on a training corpus. The drawback of this approach is that the indicators depend on the training conditions and that they are blind to the physical grounds of intelligibility.…”
Section: Introductionmentioning
confidence: 99%